Persistent organic pollutants in stomach contents of Adélie penguins from Edmonson Point (Victoria Land, Antarctica) - Corsolini, S.; Olmastroni, S.; Ademollo, N.; Minucci, G.; Focardi, S. (BACKHUYS PUBLISHERS, 2003)
Stomach contents (n=43) of Adelie penguin (Pygoscelis adeliae) nesting at Edmonson Point (Ross Sea) (74degrees20'56.7"S, 165degrees08'10.03"E) were analysed. Gas chromatography revealed concentrations of polychlorinated biphenyls (PCBs), including coplanar congeners, at 1.01 ng/g wet wt,pp'DDE at 5.80 ng/g wet wt and and hexachlorobenzene (HCB) at 4.70 ng/g wet wt. Average input of these persistent organic pollutants (POPs) through diet also was evaluated. The following concentration gradient of PCB isomer-specific classes was revealed: hepta-CB > hexa-CB > penta-CB. The most abundant congeners were PCB 189, PCB 134 and PCB 151, while PCB126 was the most abundant among coplanar PCBs. Toxic Equivalency Factors (TEFs) were also used to evaluate toxicity. Correlation was found between contamination and penguins' diet in relation to sex during the mating season, when observations took place. Foraging sites were identified by satellite trackers in two study periods.